Tradisi Kawin Lari “Silariang” Di Makassar Sulawesi Selatan Ditinjau Dari Hukum Islam Dan Undang-Undang No 16 Tahun 2019 Tentang Perubahan Atas Undang-Undang No 1 Tahun 1974 Tentang Perkawinan - Nabilah Salwa Ungawaru; Sri Poediastoeti; Faizal Adha (Bandung Conference Series: Law Studies, 2024)
Abstract. "Silariang" is a tradition of elopement in Makassar City, South Sulawesi, which is caused by refusing an arranged marriage (forced marriage), economic factors, rejected applications, bad male behavior. This occurs due to the lack of community implementation of Islamic Law and Marriage Laws. This research aims to determine the occurrence of "Silariang" and the implementation of Islamic Law and Laws. This research method is normative juridical research. The method used is qualitative analysis by analyzing documents and reports relating to the "Silariang" elopement. If a marriage is not registered with the KUA, the marriage is considered invalid according to law. When the couple meets the requirements determined by law, both internal and external requirements, the marriage is considered valid. The relationship between a man and a woman can be considered as legal husband and wife if it is based on established rules or regulations, so that the marriage is considered valid. Likewise, according to Islamic law, marriages carried out without a guardian will be considered invalid in religion. The husband-wife relationship resulting from "Silariang" without the consent of the guardian and an attitude of disagreement based on reasons in accordance with the Shari'a, shows that the perpetrator of "Silariang" has committed an incorrect action or violated religious norms. However, if they succeed in undergoing a reconciliation ceremony called "Abbaji", the woman's family will accept them back and carry out a correct marriage according to the terms and harmony. Thus, it can be understood that the husband-wife relationship resulting from "Silariang" without the consent of the guardian and an attitude of disagreement based on reasons in accordance with the Shari'a, shows that the perpetrator of "Silariang" has committed an incorrect action or violated religious norms. Abstrak. “Silariang” merupakan tradisi kawin lari di Kota Makassar Sulawesi Selatan yang disebabkan karena menolak perjodohan (kawin paksa), faktor ekonomi, lamaran ditolak, tingkah laku laki laki buruk. Terjadi karena kurangnya implementasi masyarakat terhadap Hukum Islam dan Undang-Undang perkawinan.Penelitian ini bertujuan untuk mengetahui terjadinya “Silariang” dan penerapan implemetasi terhadap Hukum Islam dan Undang-Undang. Metode penelitian ini merupakan penelitian yuridis normative. Metode yang digunakan yaitu analisis kualitatif dengan cara menganalisis dokumen dan laporan yang berkaitan dengan kawin lari “Silariang”. Perkawinan yang tidak tercatat di KUA maka perkawinan tersebut dianggap tidak sah menurut hukum. Ketika pasangan tersebut memenuhi persyaratan yang ditentukan oleh undang-undang, baik syarat internal maupun syarat eksternal maka perkawinan tersebut dianggap sah. Hubungan antara seorang pria dan seorang wanita dapat dianggap sebagai suami istri yang sah apabila didasarkan pada aturan atau ketentuan yang telah ditetapkan, sehingga perkawinan dianggap sah. Begitu pula menurut Hukum Islam perkawinan yang dilakukan tanpa wali akan di anggap tidak sah dalam agama. Hubungan suami-istri hasil dari “Silariang” tanpa persetujuan wali dan sikap tidak setuju berdasarkan alasan yang sesuai dengan syariat, menunjukkan bahwa pelaku “Silariang” telah melakukan tindakan yang tidak benar atau melanggar norma agama. Namun jika mereka berhasil menjalani acara berdamai yang disebut “Abbaji” maka keluarga pihak perempuan akan menerima mereka kembali dan melakukan perkawinan yang benar sesuai syarat dan rukun. Dengan demikian, dapat dipahami bahwa hubungan suami-istri hasil dari “Silariang” tanpa persetujuan wali dan sikap tidak setuju berdasarkan alasan yang sesuai dengan syariat, menunjukkan bahwa pelaku “Silariang” telah melakukan tindakan yang tidak benar atau melanggar norma agama